PENINGKATAN HASIL BELAJAR PKN MELALUI MODEL KOOPERATIF SNOWBALL THROWING KELAS IV SD NEGERI 163084 - Herdawati, Herdawati (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study aims to improve student learning outcomes on Civics subjects through the model of Cooperative Cooperative Type Snowball Throwing. The subject of this research is the fourth grade students of SD Negeri 163084 which amounted to 35, consisting of 18 siswalaki male and 17 female students. The results obtained from the learning with the method of Cooperative Type Snowball Throwing on Civics subjects in class IVmemiliki positive impact in improving student learning outcomes are marked by improvements in student learning completeness in each cycle, the cycle I as many as 20 students (79.69%) who get value â¥70, and in cycle II as many as 27 students (87,90%) get value â¥70, so in this case declared succeed.Keywords: learning outcomes, Civics, Co-operative Snowball Throwing model